2020
DOI: 10.1088/1361-6501/abbc8a
|View full text |Cite
|
Sign up to set email alerts
|

Optical rotation detection method based on acousto-optic modulation in an atomic spin co-magnetometer

Abstract: A new concept for probe light intensity stability control and high-frequency modulation based on an acousto-optic modulation in a K-Rb-21Ne co-magnetometer is reported. The structure and optical path are ingeniously designed to avoid the interference of zero-order diffraction light. The average rotation rate sensitivity of 7 .9 … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 7 publications
(1 citation statement)
references
References 24 publications
0
1
0
Order By: Relevance
“…In SERF co-magnetometers, atomic spin ensembles are polarized by the pump beam while the atomic spin precession signal is obtained by the probe beam [10]. In previous studies, the probe beam has always simply been regarded as a problem related to the scale factor, and it is considered to be ideally linearly polarized without interference with the spin polarization [11]. However, as studies progressed the nonlinear relationship between the probe power density and the stability of the SERF co-magnetometer suggested that the effect of the probe beam on spin polarization needed to be analyzed.…”
Section: Introductionmentioning
confidence: 99%
“…In SERF co-magnetometers, atomic spin ensembles are polarized by the pump beam while the atomic spin precession signal is obtained by the probe beam [10]. In previous studies, the probe beam has always simply been regarded as a problem related to the scale factor, and it is considered to be ideally linearly polarized without interference with the spin polarization [11]. However, as studies progressed the nonlinear relationship between the probe power density and the stability of the SERF co-magnetometer suggested that the effect of the probe beam on spin polarization needed to be analyzed.…”
Section: Introductionmentioning
confidence: 99%